Pengaruh Store Atmosphere dan Keanekaragaman Produk Terhadap Impulse Buying (Studi Kasus Pada TOP Bangunan) - Habibah Bilqis Maharani; Tri Sudarwanto (BIMA : Journal of Business and Innovation Management, 2021)
The lifestyle changingwhich affect the changingof shopping behavior in communities in urban areas makes retail shopsattracting consumers in droves by changing their marketing strategies. TOP Bangunan relies on the store atmosphere and their product diversity to increase the sales volume. Theaim of this study is to analyze the influence of the store atmosphere and their product diversity towardthe impulse buying which is a case study on TOP Bangunan. This study used quantitative data analysiswith survey data collection techniques (observation). It used primary data which is obtained from questionnaires containing 36 statement items. The population in this study was all consumers of TOP Bangunan who did the impulse buying. The sample in this study was 50 respondents by using purposive sampling technique which has some requirement, a respondent who filled out the questionnaire mustdo the  impulse buying at TOP Bangunanfor more than 17 years. The data analysis used was multiple linear regression with IBM SPSS 23. The results showed that: (1) the store atmosphere partially influences the impulse buying towardsthe consumers of TOP Bangunan  (2) the product diversity partially influences the impulse buying towardsthe consumers of TOP Bangunan, and(3) the store atmosphere and product diversity simultaneously influence the impulse buying towardsthe consumers of TOP Bangunan. Keywords: Store Atmosphere; Product Diversity; Impulse Buying